Plasmid Profile Of avian Strains Of Pasteurella Multocida - Balakrishnan G (Department of Microbiology, College of Veterinary and Animal Sciences, 1998)
Four isolates of P. multocida (DCl, DC2, FCl and FC2) from avian species (chicken and ducks) were subj ected to various typing methods like biotyping, antibiogram and plasmid profiling. The pathogenicity of the isolates was also ascertained in mice, rabbits chicken and ducks. By biotyping, the isolates were found to belong to two subspecies P. mul tocida subsp. mul tocida and P. mul t.oc i cie subsp. septica. All the isolates fermented xylose and none of them fermented dulcitol. Antibiogram of the isolates was carried out and they wer~ found to be resistant to furazolidone, metronidazole anC nalidixic acid. Some of the isolates are also resistant tc sulpha and trimethoprim. All the isolates were pathogenic to mice on rip injection. Duck isolates (DCl and DC2) were found to be pathogenic to rabbits killing them on fourth and fifth day respectively. The isolates DCl and DC2 were lethal to orally infected chicks within 48 h of administration and P. multocida could e reisolated from these birds. The same isolates killed the SiC injected ducks within 24 and 48 h.